APPLICATION OF METHODS OF TECHNICAL DIAGNOSIS IN SOLVING PROBLEMS OF CYBERNETIC PROTECTION - Kuzavkov, Vasyl (Ukrainian Information Security Research Journal, 2022)
The article substantiates the possibility of using diagnostic information based on physical and chemical processes in semiconductor structures of software and hardware - systems with embedded software of modern telecommunication systems for solving problems of cybernetic protection. The subject of the study is the process of functioning of a set of technical means for receiving, transmitting, storing and processing data in the management of a software component (a set of technical means that are a practical implementation of the OSI model) A generalized scheme of interaction between the software and hardware components of the selected type of radio-electronic equipment and the features of applying a physical approach to monitoring the technical condition of equipment for solving problems of cyber threats and cyber attacks are given. The tasks of technical diagnostics include control over changes in the state of the hardware (as a result of aging or replacement) and changes in the software (as a result of failures or interference by unauthorized persons). In any case, the tasks to be solved are related to the assessment of the actual state of the software and hardware, the forecast for the future, the assessment of the probability of failures, the risk of accidents. Based on the analysis of the values of the diagnostic parameter (in comparison with the reference or calculated values), the place of non-compliance with the established (defined) mode of operation, the causes and possible consequences are established. Decision-making is fundamentally possible in the presence of a diagnostic parameter, the presence of an adequate model of the control object (to obtain calculated data), or a sufficient number of the same type of means with the same operating conditions for statistical processing. It is proposed to use physical approaches of technical diagnostic methods to solve the following problems: – identification and authentication of telecommunication equipment; definition of atypical load at the program level. The task of improving information security necessitates the search (development) or creation of devices capable of generating electrical signals of a random (noise) nature. The non-contact induction method is considered as the main method.